About the Bicentennial: ambiguities in the Independence of Arequipa. - Felipe Mario Zapata-Delgado (2019)
This research aims to assess the contingencies and ambiguities of independence in Arequipa, where the elite and commoners were not set in a large economic gap, rather it was diffuse in economic terms, but not so within a hegemony and subordination based on concepts of honor and honesty to the rich for the poor, in this network are two key steps in entering Arequipa Pumacahua —1814— and the oath of independence —1825—, mentions historiography arequipeño patriotic capacity from some characters, which we believe false as both the mob and the elite did not want independence, only some reforms sought to improve their situation in the urban world, where if there is pressure for a deeper transformation is in the rural area. Themethodology we used is the regional history, plus archival sources used belong to repositories Arequipa Regional Archive, Archive Archbishop of Arequipa and the Municipal Archives. This research presents some results about the ambivalence of elite-mob groups multiethnic, and geographic features that allow distances appreciate a more particular national activity, coupled with the high Peru commercially. Lets see that finally the independence of Arequipa more Sucre was mandated by a statement published in the newspaper and Spring of Arequipa, a landmark of the population patriotism, it does not inhibit that there were some intellectuals, priests and people who did agree with a radical change.